Revealing a nonergodic mechanistic pattern for electron exchange between azurin and electrodes coated by nano-films under the glassy environmental conditions - Dolidze, Tinatin; van Eldik, Rudi; Khoshtariya, Dimitri (Bulletin of the Georgian National Academy of Sciences, 2019)
Fast-scan protein-film voltammetry was applied to explore interfacial biomimetic electron exchange under the environmental glass forming conditions. Gold electrodes were coated with 1-pentanethiol SAM–azurin (Az, blue cupredoxin) assemblies and placed in contact with a water-doped and buffered protic ionic melts of choline dihydrogen phosphate ([ch][dhp]), served as electrolyte media, allowing for a necessary cell conductivity under the virtually solid, semi-solid and liquid electrolyte conditions over 273–353 K, within which the electron exchange rate was studied as a function of the water amount and temperature. Exposure of the Az films to the semi-solid electrolyte greatly affected the protein’s conformational dynamics, hence the ET rate, via the mechanism occurring in the extra complicated dynamically-controlled regime. Results are compared to the earlier studies on the reference system with a conventional electrolyte, allowing for the disclosure of mutually-entangled mechanistic motifs. Under the “standard” condition (with no [ch][dhp] added), the Az biomolecule may reside in an apparently ergodic state, whereas upon adding of [ch][dhp] to allow water content ranging between 6 to 15 waters per [ch][dhp], system displays anomalous temperature dependences, suggesting that the reactive system crosses a broad, well-manifested nonergodic zone which arises from the continuous interplay (freezing/unfreezing) of ET-coupled highly cooperative conformational modes of the Az protein, inherently linked to the electrolyte’s slowest collective relaxation(s). Above this [ch][dhp] concentration, allowing the water content between 1.65 to 3.7 waters per ion pair, the system returns to a series of new, quasi-ergodic states, with each displaying virtually linear Arrhenius patterns yet with distinct parameters.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Electron exchange; Interphase; Nonergodicity; Redox protein; Self assembly